2021
DOI: 10.1111/pan.14229
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of midline catheters and peripherally inserted central catheters to reduce the need for general anesthesia in children with respiratory disease: A feasibility randomized controlled trial

Abstract: Background:The optimal intravenous device for antibiotic administration for children with respiratory disease is uncertain. We assessed the feasibility of a randomized controlled trial comparing midline catheters with peripherally inserted central catheters.Methods: Prospective, two-arm, feasibility randomized controlled trial in an Australian tertiary, pediatric hospital. Random assignment of 110 children (<18 years) to receive (i) midline catheter and (ii) peripherally inserted central catheters. Primary out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 40 publications
0
38
0
Order By: Relevance
“…Risk of bias assessment (Supporting Information: Table ) identified most studies as having a moderate to high risk of bias; most studies did not utilize random assignment. Only two studies, both randomized controlled trials, demonstrated a low risk of bias 21,22 . Per the GRADE criteria, the quality of the body of literature is low, based on high reliance on observational studies with an overall moderate risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Risk of bias assessment (Supporting Information: Table ) identified most studies as having a moderate to high risk of bias; most studies did not utilize random assignment. Only two studies, both randomized controlled trials, demonstrated a low risk of bias 21,22 . Per the GRADE criteria, the quality of the body of literature is low, based on high reliance on observational studies with an overall moderate risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…In all three studies, LPCs had a positive impact on patient/family experience. Two studies reported provider and staff experience with LPCs 21,33 . Carr et al 33 examined satisfaction in nursing staff, with an overall product rating of 4.4/5 on the basis of product quality, performance, ease of use, and education provided.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, intermittent intravenous antibiotic therapy is delivered via peripherally inserted central catheters (PICCs) 7,8 or midline catheters 9 when peripherally compatible infusion is planned for up to 4 weeks. Nowadays, long peripheral cannulas (LPC), defined (in adults) as devices longer than 6 cm and less than 15 cm, are an alternative intravenous device to administer short term peripherally compatible therapies.…”
Section: Introductionmentioning
confidence: 99%